1965
DOI: 10.1139/v65-042
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Ozonides: Iii. Ozonolysis of Ethyl 10-Undecenoate in Ethanol

Abstract: Diethyl sebacate was the major product obtained by ethanolysis of the ozonization products of ethyl 10-undecenoate in the temperature range 28 to 170 ' C. Mixed esters of sebacic acid were similarly obtained, in poor to moderate yields, by alcoholysis of the ozonization product from an alkyl ester of 10-undecenoic acid in the appropriate alcohol. Sebacic acid half esters are prepared by a similar treatment of the ozonization products from 10-undecenoic acid itself. Ester formation has been shown to proceed mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In reacting solvents (14) ester byproduct yields were lower, and yields of the expected acid products, nonanoic acid, and azelaic acid, were near-quantitative. Performic acid oxidation of 1-alkylcycloalkene ozonization products (15,24), emulsion ozonizatioll (13) of alkenes in aqueous hydrogen peroxide, and lowtemperature ozonization (25) gave smaller yields of esters. We found that catalyzed room-temperature autoxidation of isolated ozonide o r mixed ozonization products gave somewhat lower ester yields.…”
Section: Ide~zrifcatiotz Of Ozotzization Products From Oleic Acidmentioning
confidence: 99%
“…In reacting solvents (14) ester byproduct yields were lower, and yields of the expected acid products, nonanoic acid, and azelaic acid, were near-quantitative. Performic acid oxidation of 1-alkylcycloalkene ozonization products (15,24), emulsion ozonizatioll (13) of alkenes in aqueous hydrogen peroxide, and lowtemperature ozonization (25) gave smaller yields of esters. We found that catalyzed room-temperature autoxidation of isolated ozonide o r mixed ozonization products gave somewhat lower ester yields.…”
Section: Ide~zrifcatiotz Of Ozotzization Products From Oleic Acidmentioning
confidence: 99%